An Analysis of Speaking Anxiety of The Second Semester of English Foreign Language (EFL) Student of Tadulako University - Parasulu, Zikrullah; Anggreni, Afrillia; Usman, Sriati; Suriaman, Aminah (Universitas Negeri Padang, 2024)
The aims of this research is to find out the factors that cause students anxiety in speaking English and the ways that students overcome their anxiety. In this qualitative research, data was collected through Observation, Questionnaire, and Interview. Based on the three instrument that used, results showed there are several factors that cause students to experience anxiety when they want to speak, including Speaking in front of the class, Being laughed at by others, Students' beliefs about learning English, and Lack of preparation. data was collected from 181 students through a questionnaire adopted from the existing Foreign Language Classroom Anxiety Scale (FLCAS). The data showed that 89 out of 181 students experienced low levels of anxiety, 87 out of 181 students experienced medium levels of anxiety, and 5 out of 181 students experienced high levels of anxiety. This means that most students experience low to moderate levels of speaking anxiety. Furthermore, interviews were conducted with 5 students who had high levels of anxiety, to find out how they overcame the anxiety they experienced, the results of the interviews showed that there were three ways that students could do to overcome their anxiety, namely Preparation, Relaxation, and Positive Thinking. In this case the findings show that the level of speaking anxiety in 181 students of batch 2023 of the English Education study program at Tadulako University is at a low and medium level.